Household Pet Ownership and the Microbial Diversity of the Human Gut Microbiota - Kates, Ashley E.; Jarrett, Omar; Skarlupka, Joseph H.; Sethi, Ajay; Duster, Megan; Watson, Lauren; Suen, Garret; Poulsen, Keith; Safdar, Nasia (Frontiers in Cellular and Infection Microbiology, 2020)
The human gut microbiome has a great deal of interpersonal variation due to both endogenous and exogenous factors, like household pet exposure. To examine the relationship between having a pet in the home and the composition and diversity of the adult gut microbiome, we conducted a case-control study nested in a larger, statewide study, the Survey of the Health of Wisconsin. Stool samples were collected from 332 participants from unique households and analyzed using 16S rRNA sequencing on the Illumina MiSeq. One hundred and seventy-eight participants had some type of pet in the home with dogs and cats being the most prevalent. We observed no difference in alpha and beta diversity between those with and without pets, though seven OTUs were significantly more abundant in those without pets compared to those with pets, and four were significantly more abundant in those with pets. When stratifying by age, seven of these remained significant. These results suggest that pet ownership is associated with differences in the human gut microbiota. Further research is needed to better characterize the effect of pet ownership on the human gut microbiome.